Análise de três escalas observacionais utilizadas para avaliação do comportamento de crianças durante tratamento odontológico sob sedação - Moura , Larissa da Silva (2015)
The effectiveness of a sedative for pediatric dental treatment is commonly assessed through observational scales that assess the children behaviour. There is little information about the ability of a variety of scales in properly evaluate this behavior. The aim of this study was to analyze the characteristics of three scales,e,g,. Houpt Scale, Ohio State University Behavioral Rating Scale (OSUBRS) and Venham Behavior Rating Scale, to measure the behavior of preschool children during dental procedures under sedation. This study was an observational study nested to a randomized clinical trial (NCT02284204), which included 27 children between 4 and 6 years of age with early childhood caries and negative behavior in previous consultation. Participants underwent dental treatment under moderate sedation with midazolam and ketamine with or without addition of sevoflurane. The sessions were videotaped and five trained and calibrated observers watched the movies to record the behavior of children according to each scale. The data showed non-normal distribution (Shapiro-Wilk, P> 0.05); descriptive and correlation analyses were made (Spearman test). A total of 1,209 minutes of videos were observed and analyzed. Global scales (Houpt overall behavior and Venham) had closer scores of good behavior. The most frequent scores for Houpt were “no crying” and “no movement”, and for OSUBRS, “quiet”. Statistically significant correlations (P <0.05) occurred between Houpt overall behavior and Venham; Houpt overall behavior with Houpt categories movement (scores 2 and 4) and cry (scores 1, 2 and 4); Venham with Houpt movement (score 4) and cry (scores 2 and 4). OSUBRS scores 1 and 4 had high correlation coefficients with Houpt overall behavior and Venham. The Houpt overall behavior and the Venham Behavior Scale were highly correlated to measure behavior of children in dental treatment under sedation. OSUBRS showed better correlation with global scales compared to the categories of crying and movement of Houpt scale.